Fear of fertility side effects is a major cause for COVID-19 vaccine hesitance in infertile patients - Kern, Jessica; Schippert, Cordula; Fard, Delnaz; Bielfeld, Alexandra Petra; von Versen-Höynck, Frauke (Frontiers in Medicine, 2023)
Introduction: This study aims to investigate the acceptance, hesitance and attitudes of infertile patients towards the Covid-19 vaccination. Methods: An anonymous cross-sectional online survey was conducted between 28th of January to 10th of August 2022. The questionnaire consisted of 35 questions on demographics, Covid-19 vaccination status, prior concerns of the vaccinated participants and reasons for not vaccinating among unvaccinated participants, and factors influencing the decision not to vaccinate. Results: Of 406 participants who answered all 35 questions, 92.1% reported having received at least one dose of COVID-19 vaccine, 7.9% were unvaccinated. Factors associated with the decision for vaccination were full time or part time employment (p=0.05), high trust in the principle of vaccination (p<0.001), high willingness for other vaccination during fertility treatment (p<0.001) and risk factors for severe COVID-19 (p=0.007). Concerns about directly occurring adverse effects after vaccination (42.0%), about impact on own fertility (21.9%) or on the fertility treatment (27.5%) were the main concerns beforehand of vaccinated participants. Correlations between fertility concerns and mistrust in the general principle of vaccination were found. Beside general health concerns, unvaccinated participants reported fears about fertility impairment as the most important arguments against a COVID-19 vaccination (median of 5.0 on a five-point-Likert scale). Conclusion: Both vaccinated and unvaccinated participants stated having concerns and fears about side effects of the COVID-19 vaccination on their fertility. To increase patients' trust in medical recommendations, such as vaccination, to avoid mistrust in the medical system and to maintain patient’s compliance, there should be additional educational services that address infertile patients and their needs.